2014
DOI: 10.1038/ncomms4350
|View full text |Cite
|
Sign up to set email alerts
|

Differential affinity of FLIP and procaspase 8 for FADD’s DED binding surfaces regulates DISC assembly

Abstract: Death receptor activation triggers recruitment of FADD, which via its death effector domain (DED) engages DEDs in procaspase 8 and its inhibitor FLIP to form death-inducing signalling complexes (DISCs). The DEDs of FADD, FLIP and procaspase 8 interact with one another using two binding surfaces defined by α1/α4 and α2/α5 helices respectively. Here we report that FLIP has preferential affinity for the α1/α4 surface of FADD, whereas procaspase 8 has preferential affinity for FADD’s α2/α5 surface. These relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
96
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 73 publications
(109 citation statements)
references
References 41 publications
8
96
2
Order By: Relevance
“…An independent study on Fas DISC by Schleich et al [20] also showed that caspase-8/ cFLIP is more abundant than FADD, but the ratio was about five in western blot and two in mass spectrometry. In another study by Majkut et al [21], there found approximately two caspase-8/cFLIP molecules recruited for every FADD molecule in TRAIL DISC. Even though the ratio between FADD and caspase-8/cFLIP in DISC is significantly varied among these three independent studies, the common observation is that the adaptor protein FADD exists in a substantially smaller amount than the sum of tandem-DED-containing proteins, caspase-8 and cFLIP.…”
Section: Emerging View On Ded Interactions In Disc Assemblymentioning
confidence: 96%
See 4 more Smart Citations
“…An independent study on Fas DISC by Schleich et al [20] also showed that caspase-8/ cFLIP is more abundant than FADD, but the ratio was about five in western blot and two in mass spectrometry. In another study by Majkut et al [21], there found approximately two caspase-8/cFLIP molecules recruited for every FADD molecule in TRAIL DISC. Even though the ratio between FADD and caspase-8/cFLIP in DISC is significantly varied among these three independent studies, the common observation is that the adaptor protein FADD exists in a substantially smaller amount than the sum of tandem-DED-containing proteins, caspase-8 and cFLIP.…”
Section: Emerging View On Ded Interactions In Disc Assemblymentioning
confidence: 96%
“…This feature contrasts CARD-CARD binding which is based on the electrostatic interaction between H2 and H3 face (not H2-H5 face) and H1-H4 face as observed in the crystal structure of CARD-CARD complex from Apaf-1 and procaspase-9 [8]. The crystal structure of MC159-vFLIP was used as a reference for the homology modeling studies on the tandem DEDs in procaspase-8 and cFLIP, which predicted very high structural similarity between them [19,21]. Especially, the involvement of H2-H5 face should be the characteristic element of DED-DED interaction, because the alternative H2-H3 face, instead, is commonly involved in CARD-CARD and in DD-DD interactions [8,16,27].…”
Section: Structural Features Of Death Effecter Domainmentioning
confidence: 99%
See 3 more Smart Citations